The Effect of Molasses Application on Soil Biological Indicators and Maize Growth of Different Tillage Soil: A Pot Experiment - Nugroho, Priyo Adi; Prettl, Nándor; Kotroczó, Zsolt; Juhos, Katalin (Journal of Environmental Geography, 2023)
Soil enzyme activity and labile carbon (LC) have long been used as soil health indicators. Soil health can be improved by molasses addition resulting in better plant growth and productivity. The effect of molasses on soil biological activity and plant growth under different tillage soil has not been discussed in many studies in Hungary. We assessed two soil types under different long-term tillage practices: conservation tillage (CT), which leaves 30% or more residue on the soil surface, and conventional-ploughing tillage (PT). A pot experiment with maize as the crop was carried out using the composite soil (0-20 cm) of CT and PT; a randomized block design with four replications was employed. Three levels of molasses concentration, 0 g L-1, 0.05 g L-1, and 0.2 g L-1 were applied. LC, dehydrogenase (DHA), β-glucosidase activity, plant height, and dry weight biomass were measured at the end of the experiment (after eight weeks). The results indicated that LC in CT increased by 7.61-21.23% over the increase in molasses concentration. LC concentration was significantly higher in the CT than in the PT soil. β-glucosidase activity increased along with the increase of molasses concentration by 11.42-30.43% in CT and 16.03-56.67% in PT; however, the significantly different appeared only in PT soil. The molasses application affected the DHA as well. The activity of dehydrogenase increases by 39.49-80.76% and 30.43-50.59%, respectively, in CT and PT. Nevertheless, no significance occurred in the tillage system or the molasses concentration. Our study also found that the different molasses concentrations did not affect the plant height and dry weight biomass in CT and PT. However, applying each molasses concentration in CT markedly escalated the plant height and dry weight biomass compared to PT. The enhancement of soil biological activity and plant growth by the molasses application allows a promising strategy for maintaining the soil health of agricultural land.